Competitive Advantages in the Chinese Internet Industry --Cases Study from Taobao.com and eBay, Baidu and Google, QQ and MSN - CHEN, XI (2009)
This research aims to provide an overview of strategies adopted by three Chinese companies—Taobao.com, Baidu, and QQ to gain competitive advantages. Three strategies—first- and second-mover strategy, generic strategy, and resource-based theory are identified and further analyzed. The analysis employs documentary research methods, particularly firms’ historical documentary review and analysis, for this qualitative research to study each case.